2002
DOI: 10.1001/archotol.128.4.389
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Morbidity and Complications of Total Thyroidectomy

Abstract: Postoperative hypocalcemia is the most common immediate surgical complication of total thyroidectomy. Other complications, including recurrent laryngeal nerve paralysis, can be expected at rates approximating 1%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
255
4
22

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 345 publications
(294 citation statements)
references
References 19 publications
13
255
4
22
Order By: Relevance
“…Both in our study and in a study of 34 patients with thyroiditis by Bhattacharyya and Fried, the presence of concomitant lymphocytic thyroiditis with thyroid malignancy was not a risk factor for permanent hypocalcemia [17].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Both in our study and in a study of 34 patients with thyroiditis by Bhattacharyya and Fried, the presence of concomitant lymphocytic thyroiditis with thyroid malignancy was not a risk factor for permanent hypocalcemia [17].…”
Section: Discussionsupporting
confidence: 56%
“…The National Hospital Data Survey database was examined by Bhattacharyya and Fried and in their retrospective study of 517 patients; younger age was statistically associated with an increased incidence of hypocalcemia [17]. In a study of 7,266 patients with benign thyroid disease by Thomusch et al, advanced age was found to be associated with permanent hypocalcemia [6].…”
Section: Discussionmentioning
confidence: 99%
“…The impact on quality of life as well as clinical presentation of RLN paralysis mainly depends on its severity, unilateral versus bilateral nerve palsy, concomitant injury to superior laryngeal nerve, and baseline status of the vocal cords pre-operatively [15,16]. The range of the clinical severity of RLN palsy may extend from asymptomatic decrease movement of the vocal cords, hoarseness of voice, severe loss of voice, and aspiration to respiratory distress [10,15,16]. Thyroid surgery causing RLN palsy may prompt medico-legal litigations against the surgeon [1,2,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Ayrıca bütün tiroid venlerinin bağlanmış olması da venöz stazın nedenleri arasındadır. Venöz staz ve ödem bir süre için bile olsa da, paratiroid fonksiyonlarını yavaşlatır ve ameliyattan birkaç hafta sonraya kadar devam eden geçici hipoparatiroidiye sebep olabilir (24,25).…”
Section: Discussionunclassified